2016
DOI: 10.7554/elife.14712
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing control of Type VI secretion factors restricts the proliferation of quorum-sensing mutants

Abstract: Burkholderia thailandensis uses acyl-homoserine lactone-mediated quorum sensing systems to regulate hundreds of genes. Here we show that cell-cell contact-dependent type VI secretion (T6S) toxin-immunity systems are among those activated by quorum sensing in B. thailandensis. We also demonstrate that T6S is required to constrain proliferation of quorum sensing mutants in colony cocultures of a BtaR1 quorum-sensing signal receptor mutant and its parent. However, the BtaR1 mutant is not constrained by and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 33 publications
2
67
0
Order By: Relevance
“…Phosphoproteomics proved a powerful tool to uncover new aspects of T6SS regulation and led to the discovery of the regulatory interplay controlling both QS and T6SS and suggesting the possibility of the coordination between T6S and non-T6SS processes. Ultimately, the complex coordination of QS and T6SS presumably enhances the overall competitive fitness of vibrios for thriving in marine environments (Weber et al, 2009;Borgeaud et al, 2015;Majerczyk et al, 2016). Finally, by additional understanding of the regulation of T6SS activity in V. alginolyticus, we may be able to develop strategies, such as using chemicals that affect T6SS activity or interfere with QS, to reduce the competitive fitness of the bacterium and effectively control the pathogen which plagues the aquaculture industry.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoproteomics proved a powerful tool to uncover new aspects of T6SS regulation and led to the discovery of the regulatory interplay controlling both QS and T6SS and suggesting the possibility of the coordination between T6S and non-T6SS processes. Ultimately, the complex coordination of QS and T6SS presumably enhances the overall competitive fitness of vibrios for thriving in marine environments (Weber et al, 2009;Borgeaud et al, 2015;Majerczyk et al, 2016). Finally, by additional understanding of the regulation of T6SS activity in V. alginolyticus, we may be able to develop strategies, such as using chemicals that affect T6SS activity or interfere with QS, to reduce the competitive fitness of the bacterium and effectively control the pathogen which plagues the aquaculture industry.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have shown that the genetic architecture of a single trait can constrain cheating, other studies have revealed mechanisms against cheating that are based on the regulatory linkage of multiple traits (Foster et al 2004;Jousset et al 2009;Dandekar et al 2012;Ross-Gillespie et al 2015;Wang et al 2015;Majerczyk et al 2016;Özkaya et al 2018). For instance, Dandekar et al (2012) showed that mutants deficient in the LasIR quorum-sensing (QS) system in P. aeruginosa could cheat on cooperative protease production, but exhibited metabolic insufficiencies in certain media, because this QS system also controls the expression of enzymes required for nutrient degradation.…”
Section: Discussionmentioning
confidence: 78%
“…One example for how policing occurs involves Pseudomonas aeruginosa populations, in which QS cooperators produce cyanide, which inhibits the growth of QS mutants but not of the cooperators (Wang et al, 2015). Similarly, in Burkholderia thailandensis, T6SS expression is induced by QS in cooperators, which renders QS mutants susceptible to T6SS-mediated poisoning (Majerczyk et al, 2016). Whereas these mechanisms keep social mutants from exploiting public goods, they can also be used against siblings that are physiologically different.…”
Section: Physiological Recognition As a Function Of Social Integrationmentioning
confidence: 99%